2004
DOI: 10.1128/jvi.78.3.1202-1211.2004
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Elicits a Coordinated Cellular Antiviral Response via Envelope Glycoprotein B

Abstract: Previous studies have shown that human cytomegalovirus (CMV) is a potent elicitor of interferon-stimulated gene (ISG) expression. Induction of the interferon pathway does not require replication-competent virus, and envelope glycoprotein B (gB) from CMV is a viral structural component that can directly induce transcription of ISGs. Here we extend these earlier findings by defining the consequences of inducing the interferon pathway. We found that cells respond to CMV or soluble gB by establishing a functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 52 publications
(77 reference statements)
4
104
4
Order By: Relevance
“…In contrast to paramyxoviruses and retroviruses, CMV is extremely structurally complex, displaying at least 12 envelope glycoproteins. Soluble forms of envelope glycoprotein B (gB) activate NF-B (80) and IRF3, induce IFN-␤ secretion, and render an antiviral state in cells (11,12,16,71). More recently, we have found that soluble gB also induces inflammatory cytokine secretion in a TLR2-dependent manner.…”
Section: Molecular Basis Of Tlr Activationmentioning
confidence: 82%
“…In contrast to paramyxoviruses and retroviruses, CMV is extremely structurally complex, displaying at least 12 envelope glycoproteins. Soluble forms of envelope glycoprotein B (gB) activate NF-B (80) and IRF3, induce IFN-␤ secretion, and render an antiviral state in cells (11,12,16,71). More recently, we have found that soluble gB also induces inflammatory cytokine secretion in a TLR2-dependent manner.…”
Section: Molecular Basis Of Tlr Activationmentioning
confidence: 82%
“…HCMV and a soluble version of gB are able to activate IRF3 and the transcription of ISGs (32)(33)(34). Recent evidence using several strategies to deplete cellular IRF3 confirms its requirement and proposes that IRF3 is the primary transcription factor mediating HCMV-induced IFN signaling (35).…”
mentioning
confidence: 96%
“…The recently identified cytosolic DNA sensor DAI (Takaoka et al, 2007) could be involved in the TLRindependent recognition of MCMV. For HCMV, several components including gB and gH (Yurochko et al, 1995(Yurochko et al, , 1997, the TNF-receptor homologue UL144 (Poole et al, 2006) and virion-associated activated casein kinase (Nogalski et al, 2007) were reported to induce an extended activation of NF-kB and IRF3 (Yurochko et al, 1997;Boehme et al, 2004). HCMV stimulates NF-kB activity binding to HCMV promoter elements (Sambucetti et al, 1989;Sun et al, 2001), and complete repression of NF-kB signalling was found only in the late phase of HCMV replication (Jarvis et al, 2006).…”
Section: Infection Activates Ifn-a/b Inducing Signalling Pathwaysmentioning
confidence: 99%